It's the frame that matters: Immigrant integration and media framing effects in the Netherlands. (November 2016) - Bos, Linda; Lecheler, Sophie; Mewafi, Moniek; Vliegenthart, Rens
Abstract: In the past years the Netherlands have witnessed turbulent debates on immigration and integration, characterized by high levels of negativity and containing a variety of different viewpoints, i.e., frames, of the issue. We use a 4 × 2 between subjects experiment to investigate, which responses four salient immigration frames elicit among Dutch citizens. The results show that, whereas the willingness to support collective action is affected by the valence of the story, attitudes towards immigrants and intercultural behavioural intentions are affected by the frame of the story: the multicultural frame exerts positive, and the victimization frame exerts negative effects, regardless of the valence of the story.